Transforming The Thought Of The Interpretation Of The Qur'an (Revelation-Mystical-Ideological-Critical-Analogic ) - Fajria, Nura; Kholil, Asyhar (International Journal of Research, 2024)
The phenomenon of Qur'anic tafsir continues to develop and change from tafsir bil Ma'tsur to tafsir bill Ra'yi, The phenomenon of transformation and development of tafsir is inseparable from the search for meaning by readers of the Qur'anic text, namely mufassir. This transformation then gave rise to the epistemology of interpretation. This article wants to periodize the thinking of interpreters from birth to contemporary today because changes in interpretation are influenced by epistemology, the epistemology of interpretation includes reason, sources of knowledge, methods, validation, and media. From this, the question arises, (1) How to identify the frame of mind and points of thought of interpretation from classical to contemporary? (2) What is the product of the transformation of the development of Islamic thought in Tafsir? This can be traced to the development of the human way of reason in the face of the Qur'anic texts. This research uses a qualitative-descriptive method with a historical approach and theory of The Historical Idea Qur’anic interpretation by Ignaz Goldziher. From the results of the study, five eras have significant transformations, namely; the time of the Prophet who used the Era of Revelation Reason (Birth Era), in the growth of Islam the emergence of Mystical thought (Formative Era), and the golden age of Islam used Ideological reason (Affirmative Era). The modern era emerged critical reason (Reformative Era). The emergence of the new media era today, gave birth to interpretation with the contextual-analogical reason (Anological Era) of Qur'anic interpretation texts, can be seen in the audio-visual interpretation of Gus Baha' in Q.S Thaha verses 17-18.